Modified Head and Neck Swallow Scale: Using EORTC‐QLQ‐H&N35 to Predict Overall Survival. (24th April 2021) - von Allmen, Douglas; Tang, Alice; Takiar, Vinita; Zender, Chad; Romeo, Stephen; Masch, Jessica; Casper, Keith; Patil, Yash; Wilson, Keith; Khosla, Siddarth; Niu, Liang; Altaye, Mekibib; et al.
Abstract : Objectives/Hypothesis: Dysphagia is a treatment‐related complication of head and neck cancer (HNCA). We demonstrate the predictive value of a modified head and neck swallow scale (m‐HNSW) adapted from the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire‐Head and Neck 35 (EORTC‐QLQ‐H&N35). Study Design: Retrospective Cohort Study. Methods: Retrospective, single‐center cohort study utilizing a prospectively collected database of HNCA patients in a high‐volume tertiary referral center. 736 HNCA patients more than 2 years from completion of treatment were identified. EORTC‐QLQ‐H&N35 data collected from at least one of three defined episodes of care were used. The m‐HNSW uses three questions to form a 9‐point dysphagia scale. A Cox proportional hazards model was used to determine the effect of the m‐HNSW while controlling for demographics, tumor staging, site, and treatment. Results: Using data from 3, 6, 12 months from treatment, we analyzed a subset that included 328 patients. Three months after the completion of therapy, the m‐HNSW score had a significant association with 1 (HR = 1.24, P = .0005) and 5 year survival (HR = 1.19, P = .0002) after accounting for body mass index. Six (HR = 1.14, P = .014) and 12 month (hazard ratio (HR) = 1.33, P < .0001) scores post completion of therapy predict 5‐year survival. An increase of the m‐HNSW score by 1 point was associated with an increase in death by 24%, and 19% at 1 and 5 years following therapy. Conclusions: The m‐HNSW is a simple assessment of dysphagia using previously validated EORTC‐QLC‐H&N35 data that when taken at 3, 6, and 12 months after completion of therapy is predictive of overall survival. Level of Evidence: 4 Laryngoscope, 131:2478–2482, 2021